Peningkatan daya terima dan efektivitas makanan tambahan untuk balita melalui formula sereal siap seduh - Manuntun Rotua; Nathasa Weisdania Sihite (Poltekkes Kemenkes Aceh, 2024)
Background: Wasting is a nutritional deficiency issue experienced by toddlers. Providing supplementary food is one effective way to improve the nutritional status of children. This cereal, made from tempeh flour and kepok bananas, is a suitable choice for enhancing the nutritional content of cereal, especially its protein.Objectives: The aim of this research was to determine the acceptability and nutritional content.Methods: The research design used a Completely Randomized Design (CRD) with one control (FO) and three formulas (F1, F2, and F3) with percentages of 10%, 25%, and 50%. Organoleptic testing was conducted at the Food Technology Laboratory of Poltekkes Kemenkes Palembang, while nutritional analysis was carried out at the Saraswanti Indo Genetech Laboratory in Bogor. The research was conducted from June to November 2023. Statistical analysis was performed using the Kruskal Wallis test followed by the Mann-Whitney test.Results: The selected cereal was F2 (tempeh flour 25 grams, banana flour 25 grams) with proximate test results per 100 grams (energy 498 Kcal, protein 21,2%, fat 24,91%, carbohydrates 47,3%, ash content 2,98%, moisture content 3,6%). There weredifferences in aroma, color, taste, texture, and aftertaste criteria (p-value<0,05). The three formulas (F1, F2, and F3) in taste criteria (p-value<0,05), while in aroma, color, texture, and aftertaste criteria, differences were found between only 2 formulas.Conclusion: The treatment formulas showed differences, especially in the taste criteria. F2 was selected as the preferred cereal formula through hedonik testing. Cereal F2 serves as an alternative supplementary food for toddlers with digestive problems or difficulty chewing, as it is practical, easy to serve, and cost-effective.